Implications of The Development of The Mandalika Circuit For The Economic And Social Community - Aulad, Afdalul; Manzilati, Asfi (Journal of International Conference Proceedings, 2023)
This research aims to identify and analyze the implications of building the Mandalika circuit for the economy and society. The method used in this study is descriptive qualitative, with data collection through interviews. The results of this study are Culture is the whole system of ideas, actions and results of human work in the life of society which is made the property of humans by learning. As for human actions which are not learned, such as instinctive actions, some reflexes, some human actions which are instinctual abilities that are carried in the genes with their birth (such as eating, drinking, or walking on their two legs), are also remodeled by them into cultural actions.